Pathology of Resolving Polyomavirus‐Associated Nephropathy. Issue 6 (30th May 2013) - Menter, T.; Mayr, M.; Schaub, S.; Mihatsch, M. J.; Hirsch, H. H.; Hopfer, H.
Abstract: Control of polyomavirus BK (BKV) is achieved by reducing immunosuppression allowing an effective BKV‐specific T‐cell response. The morphology of resolving BKV‐associated nephropathy (PyVAN) has not been systematically investigated. Ninety‐nine surveillance biopsies of 35 patients with BKV viremia treated exclusively by immunosuppression reduction were scored according to Banff criteria and grouped relative to BKV viremia as pre‐, increasing, decreasing and post‐BKV viremia. Thirty‐four of 35 patients (97%) cleared BKV viremia after a median of 9 months posttransplantation. The tubulitis score, extent of tubules with intraepithelial lymphocytes, and interstitial inflammation significantly increased from the time of increasing to decreasing viremia. Tubulointerstitial inflammation, to a lower extent, persisted after clearance. The number of SV40+ tubules correlated with the BKV load in plasma, but SV40 immunohistochemistry was frequently negative (60%). During decreasing viremia, 31% of PyVAN cases were plasma cell‐rich and 40% showed tubular HLA‐DR expression. Compared to baseline 1 month posttransplantation, allograft function remained stable or improved in 29/35 patients (83%) after a median follow‐up of 48 months. Within 1 year after clearance of BKV viremia, clinical rejection occurred in 2/35 patients (6%). Our data suggest that resolving PyVAN is typically characterized by a self‐limiting acute interstitial nephritis, morphologically indistinguishable from interstitial rejection. Abstract : This study analyzes the histological features associated with the resolution of polyomavirus nephropathy, and shows that resolution is regularly associated with a significant increase in intraepithelial lymphocytes and interstitial infl ammation, morphologically indistinguishable from interstitial rejection. See editorial by Randhawa on page 1379.